THE EMPOWERMENT OF PRODUCTIVE ZAKAT IN IMPROVING THE QUALITY OF MUSTAHIK EDUCATION - Abramuthiah, Sinta; Lise Purnamasari,; Afiatin Dewi, (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Productive zakat is the management and distribution of zakat funds that have long-term effects on zakat recipients and are invested in productive activities. This study aims to determine the role of productive zakat empowerment in improving the quality of mustahik education. This is reviewed based on graduate competency standards, educational assessment standards, and infrastructure standards. The research methodology employed in this study is qualitative research with a descriptive approach. Data collection techniques include focus group discussions (FGDs), interviews, and document analysis. The data analysis procedure employed in this study utilized the Miles and Huberman data analysis model. The findings of this study indicate that productive zakat empowerment is a significant factor in enhancing the quality of mustahik education through scholarship programs aligned with three national education standards. In accordance with the graduate competency standards, students are expected to complete the memorization of 30 juz of the Qur'an. In terms of educational assessment, students have demonstrated a notable enhancement in their academic performance, as well as an improvement in their ability to memorize the Quran. With regard to the standard of facilities and infrastructure, students who previously experienced economic difficulties are now experiencing changes due to the scholarship program. As a result, students are now able to pay school fees and have access to complete school equipment, including books and school uniforms, which optimally supports their learning process.